INCREASING LEADERSHIP ROLE IN MAINTAINING AND IMPROVING EMPLOYEE MORALE IN PT. AA: INCREASING LEADERSHIP ROLE IN MAINTAINING AND IMPROVING EMPLOYEE MORALE IN PT. AA - Richard Han (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2021)
The purpose of this research is to find the best recommendation for the moral crisis that PT. AA is facing and avoiding problem in the future. Facing moral crisis can giving away new business opportunity, time wasted, and energy that is not allocated correctly for the expansion of the business instead the efforts are directed to end the problem that is currently happening. The methodology that used is qualitative with interpretivism paradigm. To obtain the critical data about morale and value of the employee are needed to have an interview, observation and data collection. The result of this research found that top-level management changed their strategy in these past few years and the leadership is considered enough influential but not authoritarian and not proactive. For the employee's morale in this company is considered marginal while they are not attached to their company and didn’t have a good sense of belonging.